Optimalisasi Energi Terbarukan: Transformasi Listrik di Ma’had Al-Jami’ah UIN Raden Intan Lampung Melalui Panel Surya - Mughofar, Ahmad; Lia, Vina Puspita; Kuswanto, Eko (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2023)
The continuous utilization of fossil energy has resulted in serious impacts on the environment and the Earth. In order to reduce the use of environmentally harmful fossil energy, UIN Raden Intan Lampung, as one of the eco-friendly campuses in Indonesia, is committed to transitioning to renewable energy, particularly through the use of solar panels to generate electrical energy. The aims of this research were to evaluate the effectiveness and utilization of solar panels in the male dormitory building of Ma’had Al-Jami’ah UIN Raden Intan Lampung in meeting electricity needs. The research methodology involves observation, interviews, and questionnaire completion as data collection efforts. The research findings indicate that solar panels generate an average of 381.33 watts of electricity per day, equivalent to 13.24% of the maximum electrical power that can be produced. However, the contribution of solar panels covers only 0.20% of the total electricity needs in the male dormitory building. Upon further analysis, the effectiveness of solar panels in meeting electricity needs, particularly for lighting in the building, is only 13.94%. Therefore, it can be concluded that the contribution of electrical energy generated by solar panels to the total and lighting needs in the male dormitory building is considered